Concept, Content, and Context Perspectives of Quality of Agrofood Products: Reflections on Some Consumer Decision-Making-Purchase Scenarios - Okpala, Charles Odilichukwu R.; Korzeniowska, Małgorzata (Frontiers in Nutrition, 2020)
Quality attributes in agrofood products can be somewhat difficult to identify and observe. The quality of the same agrofood product would likely not be exactly the same in one market shelf compared to the other. There are quality attributes peculiar/specific to one product, which stands it unique from the other. The basics/fundamentals underlying such peculiarities/specificities can be found either in concept, content, and context perspectives of quality. It appears however that no publication has deliberated on these three aspects together, that is,  concept, content, and context perspectives of quality of agrofood products, particularly on how it contributes to the decision-making of purchase an agrofood product. Therefore, we specifically look at concept, content, and context perspectives of quality of agrofood products, with a specific interest in some reflections on some consumer decision-making-purchase scenarios. Each of these, ‘concept’, ‘content’, and ‘context’ perspectives independently project very important meanings to the quality of agrofood products. There appears a thin line that would separate concept, content, and context perspectives of quality in the choice/decision-making of purchase of agrofood products. To solely depend on either concept, content, or context perspective of quality will likely provide the consumer with insufficient information about the (given/specific) agrofood product. Interaction between any two will most likely improve the information. Obviously, the interaction between the three, would most likely provide sufficient information about the quality and help consumers make a more informed decision of purchase.